Medicinal products used for the treatment and prophylaxis of COVID-19 - Vaitkevičius , A. (Neurologijos seminarai, 2020)
Currently, the most relevant public and personal health problem is the new coronavirus-induced COVID-19 disease. In view of the pandemic emergency situation, the rapid spread of the infection, the severe condition of some patients, and the high mortality rate, there is an urgent need to treat patients with both symptomatic measures and specific agents. However, to date, no medicinal products have been authorized specifically for the treatment of COVID-19. New information on the efficacy of certain medicines appears almost daily yet it is often contradictory, and reliable data from large-scale clinical trials are still lacking. The article summarizes the known data on the efficacy and safety of antiviral agents and medicines used to control immune responses, precautions and possible adverse effects on the nervous system, which could be beneficial to the physicians in clinical practice. Data on newly initiated clinical trials on medicinal products for the treatment and prevention of COVID-19 are also provided.